Development and distribution : structural change in South East Asia - Sumner, Andrew, 1973- (Oxford University Press, 2018)
Using Malaysia, Indonesia, and Thailand as examples, this book focuses on industrialization in South East Asia. These nations have all undergone a major transformation from being poor, agrarian countries to middle-income countries with a developed industrial and manufacturing base. Development and Distribution seeks to explain why and how.